Effect of particle size and volume fraction of the reinforcement on the microstructure and mechanical properties of friction welded MMC to AA 6061 aluminum alloy - Kirik, I.; Ozdemir, N.; Caligulu, U. (Redakcia Kovove Materialy, 2013)
The aim of this study is to evaluate the welding characteristic of friction welded dissimilar joints of an aluminum matrix composite Al-5%Cu-SiCp to AA 6061 aluminum alloy. Specimens of 12 mm diameter were used to fabricate the joints. The friction welding tests were carried out using a direct-drive type friction welding machine. After friction welding, the joining performance of the aluminum matrix composite Al-5%Cu-SiCp to AA 6061 friction welded joints was studied, and the effect of the particle size on the microstructure and mechanical properties of the friction welded joints was also estimated. The experimental results indicate that aluminum matrix composite and AA 6061 aluminum alloy can be joined, eventually, the particle size and volume fraction of the reinforcement play the major role in the tensile strength of friction welded joints.
Keywords: friction welding; metal matrix composites; mechanical properties